Analysis on The Effect of Compensation, Discipline and Motivation Toward Performance of Employees of Mandiri Utama Sejahtera Corporation - Rahmi Hermawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims in examining the problem of employee performance that has decreased. The main objective of this research is to find out the phenomenon and to obtain empirical evidence and conclusions about the effect of compensation, discipline and motivation toward the performance of employees of Mandiri Utama Sejahtera corporation. This research uses a quantitative design method, explanatory research, by testing the survey technique hypothesis, the questionnaire uses a Likert scale of 4, using a saturated sample, which means using the entire population of 96 employees with headquarters and 5 warehouses in several areas. The results of the study were processed using data analysis techniques: (1) validity and reliability tests; (2) classic assumption test (normality, homogeneity, heteroscedasticity and multicollinearity test); (3) coefficient of determination (R2); (4) simple and multiple regression models; (5) hypothesis testing with partial test (t test) and simultaneous (F test).  Based on the results of the study it was found that the F test showed a very significant effect on the compensation variable (X1), the discipline variable (X2), and the motivation variable (X3) together on the Performance variable (Y). This is evidenced by the calculated Fcount (49,460)> Ftable (2.70) and the significance is less than 5% (0,000 <0.05). R value (correlation) is 0.786 and R Square value (determination) is 0.617, indicating that the variable Y (employee performance) is influenced by variable X1 (compensation), variable X2 (discipline), and variable X3 (motivation) together, of 61.70% and the remaining 38.30% is influenced by other factors not examined. So the conclusion of the research results shows that there is a positive and significant influence of compensation, discipline and motivation on the performance of employees of Mandiri Utama Sejahtera corporation.